2021
DOI: 10.1002/da.23200
|View full text |Cite
|
Sign up to set email alerts
|

Forks in the road: Definitions of response, remission, recovery, and other dichotomized outcomes in randomized controlled trials for adolescent depression. A scoping review

Abstract: Background: Definitions of dichotomous outcome terms, such as "response," "remission," and "recovery" are central to the design, interpretation, and clinical application of randomized controlled trials of adolescent depression interventions.Accordingly, this scoping review was conducted to document how these terms have been defined and justified in clinical trials. Method: Bibliographic databases MEDLINE, Embase, APA PsycInfo, and CINAHL were searched from inception to February 2020 for randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…An analysis of 350 clinical trials for depression using the MADRS identified that 28 different thresholds were used to determine whether patients have MDD and should therefore be included in a given trial; thresholds ranged from total scores of 5 to 34 points 36 . Similarly, a review of 29 trials for adolescent MDD identified 47 unique definitions of remission, with only a minority of trials providing a rationale for their cut-offs 51 . Overall, this illustrates that the internal structure of the most commonly used depression instruments does not support the use of cut-offs to identify the presence or absence of MDD.…”
Section: Internal Structurementioning
confidence: 99%
“…An analysis of 350 clinical trials for depression using the MADRS identified that 28 different thresholds were used to determine whether patients have MDD and should therefore be included in a given trial; thresholds ranged from total scores of 5 to 34 points 36 . Similarly, a review of 29 trials for adolescent MDD identified 47 unique definitions of remission, with only a minority of trials providing a rationale for their cut-offs 51 . Overall, this illustrates that the internal structure of the most commonly used depression instruments does not support the use of cut-offs to identify the presence or absence of MDD.…”
Section: Internal Structurementioning
confidence: 99%
“…The most common examples of depression outcomes were continuous outcomes of symptom reduction on a scale score over time or dichotomous outcomes of response or remission. 19 Regardless of treatment exposure, response was most often defined as a specified percentage decrease in depression scale scores (eg, 50% reduction on the CDRS-R) or a rating of much improved or very much improved on the Clinician's Global Impression-Improvement subscale. 26 Remission was most often defined by an end point scale score below a specific cutoff or no longer meeting criteria for major depressive disorder.…”
Section: Introductionmentioning
confidence: 99%
“…26 Remission was most often defined by an end point scale score below a specific cutoff or no longer meeting criteria for major depressive disorder. 19 Greater reduction in symptom scale scores over time or greater proportions of responders and/or remitters represented favorable outcomes. Predictors, moderators, and mediators associated with other outcomes (eg, suicidal ideation, function) were not extracted in this review.…”
Section: Introductionmentioning
confidence: 99%
“…3) Outcome: the studies reported one or more of the following outcomes, including changes in depression scores compared to baseline, relief of depressive symptoms, or rate of adverse events. There is currently no unified standard for outcome measurement ( 35 ). Based on the current research status, we have developed the following criteria.…”
Section: Methodsmentioning
confidence: 99%